Challenges for future food systems: from the Green Revolution to food supply chains with a special focus on sustainability - Soria‐Lopez, Anton (2023)
Finding a food system to feed the growing worldwide population remains a challenge, especially in the current era, where natural resources are being dramatically depleted. From a historical point of view, the Green Revolution, together with biofortification and sustainable intensification, was established as a possible solution to counter hunger and malnutrition during the second half of the 20th century. As a solution, to overcome the limitations attributed to the Green Revolution, food supply chains were developed. The current food system, based on the long food supply chain (LFSC), is characterized by globalization, promoting several advantages for both producers and consumers. However, LFSC has been demonstrated to be unable to feed the global population and, furthermore, it generates negative ecological, environmental, logistical, and nutritional pressures. Thus, novel efficient food systems are required to respond to current environmental and consumers’ demands, as is the case of short food supply chain (SFSC). As a recently emerging food system, the evaluation of SFSC sustainability in terms of environmental, economic, and social assessment is yet to be determined. This review is focused on the evolution of food supply systems, starting from the Green Revolution to food supply chains, providing a significant perspective on sustainability.